Potential expanded pollinator distributions in North America under future climate - Brice B. Hanberry (Ecological Solutions and Evidence, 2025)
Abstract Pollinator species have declined globally during the last several decades due to a variety of factors, including habitat destruction and degradation, pesticides, disease and climate change. To examine the effects of climate change on pollinator distributions, I modelled summer occurrences of pollinator species from North America under current climate (i.e. years 1981–2010) and predicted potential climate space for current, past (20, 10 and 6 thousand years ago) and future (six projections during 2071–2100, with North American warming of 4.3°C–8.8°C) climates. Accuracies ranged in mean values from 0.93 for 12 fly species, 0.94 for 88 butterfly, 69 moth, and 17 wasp species, to 0.95 for 18 bee and 24 beetle species. Mean annual temperature was the most important variable for the greatest number of species. Centres of distributions moved about 500–650 km northwards during the interval from 20 ka to the current climate, which is similar to or less than shift distances, ranging from 500 km to 1350 km, predicted by end‐of‐century warming relative to the current climate. Generally, potential species losses, for these species overall centred in the United States, were indicated in Mexico, Central America, the Caribbean and most of the eastern half of the United States, relative to the number of species predicted under the current climate. The greatest absolute number of species was predicted to be lost in the eastern half of the United States. However, according to predictions, most pollinator species, including monarch butterflies (Danaus plexippus), may gain potential climate space in the future. Shifting to new locations is an additional challenge of climate change, particularly given current population declines under a range of stressors. Solution. Management, restoration and citizen participation to provide resources and reduce stressors are ecological solutions to support declining pollinators and pollinator distribution shifts in response to climate change.